2002
DOI: 10.1023/a:1014465611487
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The inflammatory action of jararhagin, a hemorrhagic metalloproteinase from Bothrops jararaca venom, was studied in mice using dorsal air pouches. The injection of the toxin in 6-day-old air pouches resulted in a leukocyte accumulation comparable to that induced by LPS and whole venom. Polymorphonuclear and mononuclear cells were present in this infiltrate, with a predominance of neutrophils. Treatment of jararhagin with 1,10-phenantroline abolished its proteolytic activity and reduced the pro-inflammatory eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
4

Year Published

2003
2003
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(20 citation statements)
references
References 15 publications
0
16
0
4
Order By: Relevance
“…Studies using MMP inhibitors have already confirmed the importance of the catalytic activity for the proinflammatory activity of SVMPs in experimental mice models. Leukocyte infiltrates induced by Jararhagin or BaP1 were reduced by treatments with chelating agents, such as o-phenanthroline or EDTA, respectively [8,35]. Escalante et al [5] tested the action of Batimastat, a broad-spectrum synthetic inhibitor of MMPs, in local damage induced by BaP1 and observed a reduction in bleeding, dermonecrosis and edema in mouse models.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies using MMP inhibitors have already confirmed the importance of the catalytic activity for the proinflammatory activity of SVMPs in experimental mice models. Leukocyte infiltrates induced by Jararhagin or BaP1 were reduced by treatments with chelating agents, such as o-phenanthroline or EDTA, respectively [8,35]. Escalante et al [5] tested the action of Batimastat, a broad-spectrum synthetic inhibitor of MMPs, in local damage induced by BaP1 and observed a reduction in bleeding, dermonecrosis and edema in mouse models.…”
Section: Discussionmentioning
confidence: 99%
“…SVMPs are zinc-dependent enzymes, classified in three classes, based on their precursors: the PI-class is composed of the pre-, pro-and metalloproteinase domains; PII-class of pre-, pro-, metalloproteinase and disintegrin domains; and PIII-class composed of pre-, pro-, metalloproteinase, disintegrin-like and cysteine-rich domains [4]. The PI-and PIII-classes are widely expressed in viper venoms and well characterized for their proinflammatory action, which is frequently associated with their catalytic activity [5][6][7] or with the activation of inflammatory cells as macrophages that release proinflammatory mediators [8,9]. Due to their catalytic activity, SVMPs may also have action on endogenous pro-metalloproteinases and pro-cytokines, such as pro-MMPs [10] and pro-TNF-α [11], which, upon cleavage by SVMPs, are released in their active form.…”
Section: Introductionmentioning
confidence: 99%
“…This observation led us to investigate the proinflammatory and edema-inducing properties of nsPLA 2 . Whereas these effects are known (14,37,38), little had been done to decipher the molecular determinants involved in venom PLA 2 -induced inflammation and edema, especially in the lungs.…”
Section: Discussionmentioning
confidence: 99%
“…The toxin evoked local migration of leukocytes dependent on macrophages, since injection of the toxin in 1 hr pouches, absent of resident cells, did not induce cellular influx. This pattern of response is reversed by co-injection of peritoneal macrophages with the toxin into the cavity [146]. Jarastatin, a disintegrin RGD containing peptide rich in cystein domains isolated from Bj snakes, is chemotactic to neutrophil in vitro by interfering with intracellular locomotion machinery.…”
mentioning
confidence: 99%